PROM and it’s maternal outcome: a retrospective study in a rural medical college of India - Sarkar, Malay; Mondal, Tanushree; Sarkar, Manojit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Premature rupture of membrane is the unconstrained break of layer before the beginning of labor and can happen any gestational age even at 42 weeks of growth. Around 2-30 % of all pregnancy will encounter PROM and prompts 33% of preterm birth. The analysis of PROM is to a great extent clinical and is normally proposed by a history of watery vaginal discharge and affirmed on sterile speculum assessment. This examination was led to decide the occurrence, to discover the age, equality dispersion, gestational age dissemination, presentation of PROM and plan the line of the management. Methods: The cases selected in this study were those who had spontaneous rupture of membrane after 28 weeks of gestation but before the onset of labor pain. The study period was of one year from 1st January 2019 to 31st December 2019. The study was conducted in the labor room complex of Coochbehar Govt. Medical College and Hospital, WB India. The patients were admitted in the labor room through emergency. All datas were collected from labor room log book. Results: Total no. of deliveries were 10900 and total no of PROM were 545.Incidence of PROM is 5% in the present study. Maximum no of cases were in the age group between 20-29yr (63%). PROM mainly occurs in primigravida (50.45%). And low rupture of membrane was 91.8%. Cephalic is the commonest presentation (85%) in PROM and the incidence of caesarean section is 24.95%. Conclusions: PROM is the obstetric emergency and once the PROM is diagnosed it is important to weigh the risk of PROM and prematurity and make the right choice of conservative management and active management. If there is chance of maternal morbidity pregnancy should be terminated considering the maternal wellbeing first and then that of the fetus.